Possible Novel Therapeutic Targets in Lymphangioleiomyomatosis Treatment - Song, Xixi; Cai, Hui; Yang, Chengyu; Xue, Xiaomin; Wang, Jian; Mo, Yuqing; Zhu, Mengchan; Zhu, Guiping; Ye, Ling; Jin, Meiling (Frontiers in Medicine, 2020)
Lymphangioleiomyomatosis (LAM) is a rare systemic neoplastic disease that exclusively happens in women. Studies focusing on LAM and tuberous sclerosis complex (TSC) have made great progress in understanding the pathogenesis and searching for treatment. The inactive mutation of TSC1 or TSC2 is found in patients with LAM to activate the crucial mammalian target of rapamycin (mTOR) signaling pathway and result in enhanced cell proliferation and migration. However, it does not explain every step of tumorgenesis in LAM. Since cessation of rapamycin would break the stabilization of lung function or improved quality of life and lead to disease recurrent, continued studies on the pathogenesis of LAM are necessary to identify novel targets and new treatment. Researchers have found several aberrant regulations that affect the mTOR pathway such as its upstream or downstream molecules and compensatory pathways in LAM. Some therapeutic targets have been under study in clinical trials. New methods like Genome-wide association studies (GWASs) have located a novel gene related to LAM. Herein, we review the current knowledge regarding pathogenesis and treatment of LAM and summarize novel targets of therapeutic potential recently.